Accuracy of Nurse-Performed Lung Ultrasound in Patients With Acute Dyspnea: A Prospective Observational Study. Issue 9 (March 2016) - Mumoli, Nicola; Vitale, Josè; Giorgi-Pierfranceschi, Matteo; Cresci, Alessandra; Cei, Marco; Basile, Valentina; Brondi, Barbara; Russo, Elisa; Giuntini, Lucia; Masi, Lorenzo; Cocciolo, Massimo; Dentali, Francesco
Abstract : Abstract: In clinical practice lung ultrasound (LUS) is becoming an easy and reliable noninvasive tool for the evaluation of dyspnea. The aim of this study was to assess the accuracy of nurse-performed LUS, in particular, in the diagnosis of acute cardiogenic pulmonary congestion. We prospectively evaluated all the consecutive patients admitted for dyspnea in our Medicine Department between April and July 2014. At admission, serum brain natriuretic peptide (BNP) levels and LUS was performed by trained nurses blinded to clinical and laboratory data. The accuracy of nurse-performed LUS alone and combined with BNP for the diagnosis of acute cardiogenic dyspnea was calculated. Two hundred twenty-six patients (41.6% men, mean age 78.7 ± 12.7 years) were included in the study. Nurse-performed LUS alone had a sensitivity of 95.3% (95% CI: 92.6–98.1%), a specificity of 88.2% (95% CI: 84.0–92.4%), a positive predictive value of 87.9% (95% CI: 83.7–92.2%) and a negative predictive value of 95.5% (95% CI: 92.7–98.2%). The combination of nurse-performed LUS with BNP level (cut-off 400 pg/mL) resulted in a higher sensitivity (98.9%, 95% CI: 97.4–100%), negative predictive value (98.8%, 95% CI: 97.2–100%), and corresponding negative likelihood ratio (0.01, 95% CI: 0.0, 0.07). Nurse-performed LUS had a good accuracy in the diagnosis of acute cardiogenic dyspnea. Use of this technique in combination with BNP seems to be useful in ruling out cardiogenic dyspnea. Other studies are warranted to confirm our preliminary findings and to establish the role of this tool in other settings. Abstract : Supplemental Digital Content is available in the text